Debt Financing in Russian Middle-Sized Companies - Виктория Артуровна Черкасова; А. А. Батенкова (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
This clause reveals conceptual representation of risk at the strategic point of view. The basic strategic risks of the company and the approaches connected with their estimation are also considered. The model measuring strategic risk through probability of losing the position of the company in a rating among other firms is offered.